EKSTRAK DAUN TEH HITAM SEBAGAI ANTIOKSIDAN ALAMI MINYAK KELAPA BLACK TEA LEAVES EXTRACT AS A NATURAL ANTIOXIDANT IN COCONUT OIL - Agnes Belinda Ferina; Tjandra Pantjajani; Ruth Chrisnasari (CALYPTRA, 2018)
Coconut oil can undergo rancidity during the usage. Rancidity in coconut oil can occur due to the oxidation process. Antioxidant mostly used to prevent oil oxidation. Synthetic antioxidant usually used as a preservative in commercial oil, however synthetic antioxidant had been known to cause several health problems. Therefore, this research was aimed to study the addition of antioxidant from crude extract of black tea leaves in coconut oil quality which treated to accelerate its rancidity. Black tea leaves were extracted using 3 different solvents to determine the best solvent to extract the antioxidant from black tea leaves which gave the highest antioxidant activity. The best solvent to extract the black tea leaves was found to be ethanol 96% with the antioxidant activity of 75,01%. As much as 0,01% (v/v) crude extract of black tea leaves then used for treatment to prevent the deterioration of coconut oil. The oil quality was assessed by measuring iodine value, peroxide value, TBA value and the change in colour and viscosity. The results showed that the addition of crude extract from black tea leaves delayed the oxidation rate in coconut oil compared to the control (without extract addition). The antioxidant efficiency of crude extract from black tea leaves was 1,5.